Turkic mythology in E. Tursunov's novella “Kelin” - Sabyrzhanova, Mereke S.; Ananyeva, Svetlana V. (The New Research of Tuva, 2024)
The article analyzes the novel “Kelin” by the modern Kazakh writer Ermek Tursunov, which addresses the origins of the existence of Turkic peoples and reflects ancient Turkic mythological ideas about the world order in its artistic ontology. The story's world includes zoomorphic and cosmic images that resemble the plots and episodes from ancient Turkic mythology, forming a unity with the earthly world. These images embody various aspects of the mythical order, while products and objects also hold mythological significance.The few images of the heroes are placed in a mythically significant space. Each character represents one of the fundamental roles: the continuation of the family, the protector, the provider, the guardian of the hearth, and the keeper of traditions. Among the mythically significant zoomorphic images, the figure of a totemic animal, the she-wolf, stands out. This image appears in the ancestral myth as the progenitor of the Turkic people.The mythological contexts recaptured in the story reinforce the allegorical theme of the work. The genre poetics of the text is characterized by a reduction of socio-political realities, the prevalence of mythological and traditional principles. The idea of continuity within the genre forms the basis for the semantic structure of the story.
Keywords: Kelin; Ermek Tursunov; myth; Turkic mythology; mythopoetics; Kazakh literature